Investigation on mechanical and tribological behaviour of titanium diboride reinforced martensitic stainless steel - M Sadhasivam; N Mohan; Sankara Raman Sankaranarayanan; S P Kumaresh Babu (Materials Research Express, 2020)
The role of metal matrix composites (MMCs) has gained huge momentum in various researches as well as in industrial applications due to their high stiffness and higher strength to weight ratio. It helps in achieving enormous weight reduction without compromising the strength of the material. In this study, a novel attempt was made to fabricate MMCs with martensitic stainless steel as matrix and titanium diboride (TiB _2 ) as reinforcement. The AISI 420 matrix with different weight percentages (1%, 2%, and 4%) of TiB _2 reinforcement was fabricated by vacuum induction melting technique (VIM). The aim of this study was to analyze the influence of TiB _2 particle addition on the mechanical and tribological properties of AISI 420 composites. X-ray diffraction studies revealed the presence of TiB _2 phase in the composite along with peak shifting and broadening of the steel matrix due to induced strain. Optical microscopy showed the distribution of TiB _2 particles in the matrix along with a significant amount of grain refinement of the composite due to the addition of TiB _2 . Microhardness results showed that the presence of TiB _2 improved the hardness with AISI 420/4%TiB _2 composite possessing the maximum hardness. Tensile test results indicated a significant improvement in the ultimate tensile and yield strength of the composite with the addition of TiB _2 . The wear tests were carried out on a pin on disc tribometer for various loads at a different sliding distance for steady sliding velocity. The dispersion of TiB _2 particle helped in achieving better wear resistance of the composites. Wear surface morphology was carried out to explore the wear mechanisms. Among the various wear mechanisms, abrasion and oxidation phenomena dominated in the composites. Taguchi optimization technique predicted that wt% of TiB _2 and applied load as influencing factors on the wear rate of the material.